Effects of xylanase and wheat middlings in diets for finishing pigs - C Feoli; C R Monge; C L Jones; C W Starkey; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2006)
A total of 312 finishing pigs (average initial weight of 142 lb) were used in a 62-d experiment to determine the effects of xylanase and wheat middlings on growth performance, nutrient digestibility, and carcass characteristics. Treatments were a control diet based on corn-soybean meal, without and with 750 g/ton xylanase product (to supply none and 1,050 units of xylanase activity per lb of diet), and wheat middlings (none, 15%, and 30%) arranged as a 2 × 3 factorial. The pigs were sorted by sex and ancestry and blocked by weight, with 13 pigs/pen and 4 pens/treatment. Feed and water were provided on an ad libitum basis until the pigs were killed (average weight of 266 lb) at a commercial slaughter facility. Overall, there were no interactions among xylanase addition and concentration of wheat middlings in the diet for ADG, ADFI, F/G, dressing percentage, last-rib backfat thickness, or percentage carcass lean (P>0.26). For main effects, addition of xylanase did not change growth performance or carcass measurements (P>0.16), but, as concentration of wheat middlings was increased from none to 30%, there were linear decreases in overall ADG (P0.12). In conclusion, increasing the concentration of wheat middlings, in diets from none to 30% reduced growth performance and nutrient digestibility in finishing pigs. Addition of xylanase did not prevent these negative effects.; Swine Day, 2006, Kansas State University, Manhattan, KS, 2006
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-83-S; Swine day; 2006; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 966; Finishing pig; Wheat middlings; Xylanase; Swine